Phytochemical characterization and anti-arthritic potential of Croton bonplandianus leaves extract: In-vivo and in-silico approach - Erum Javed; Humaira Majeed Khan; Qumar Shahzad; Yasser Shahzad; Hina Yasin; Zaheer Ul-Haq; Mobina Manzoor; Muhammad Usman Ghori; Amer M. Alanazi; Azmat Ali Khan (Elsevier, 2023)
Croton bonplandianus, a natural source traditionally used for treating various illnesses, including rheumatoid arthritis, was evaluated in this study. The effects of ethanolic extracts (CBEE) and aqueous fractions (CBAF) of C. bonplandianus leaves on arthritis-induced inflammation were studied using an albino rat model of inflammation induced by Freund's complete adjuvant. Eight test groups (n = 5 per group) and one vehicle control were used to evaluate the antiarthritic effects of different doses of CBEE and CBAF (125 mg.kg−1, 250 mg.kg−1, and 500 mg.kg−1) on days 5, 10, 15, and 20 compared to arthritic and vehicle controls. Arthritis severity was assessed using macroscopic arthritis grading, histological analysis, body weights, and paw thickness. CBEE and CBAF were found to reduce the prevalence of arthritis, increase body weight, and decrease paw inflammation compared to the vehicle control group by the 23rd day. In addition, they showed no effect on biochemical parameters, but a significant difference (p < 0.05) in hematological parameters compared to the arthritic control group. The study identified Hentriacontane compound as a potential contributor to the anti-inflammatory effect of C. bonplandianus, as it showed the lowest dock score for IL-1β and IL-6. Palmitoylethanol amide was identified as a potential contributor to the anti-inflammatory effect of TNF-α. Gene expression of IL-6, IL-1β, and TNF-α was down-regulated significantly (p < 0.05) in a dose-dependent manner in all treatment groups compared to the arthritic control group. In conclusion, this study validated the anti-arthritic and anti-inflammatory properties of CBEE and CBAF in a time and dose-dependent manner.